FURTHER STUDIES ON GENUS Cyphanta WALKER (PLATYCHASMATINAE: NOTODONTIDAE: LEPIDOPTERA) FROM INDIA - KALEKA, AMRITPAL SINGH; KUMAR, RISHI RISHI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The taxonomic position of genus Cyphanta Walker in subfamily Platychasmatinae and family Notodontidae has been justified. The external morphological characters including the genitalic features of Cyphanta xanthochlora Walker has been studied and illustrated in detail and the genus diagnosis has also been updated.